Respostas

2014-04-24T15:55:07-03:00
Olá. Vamos lá então :
a) 3 x +  x^{3}  -> para x = 4
      3 . 4 + 4 ³ =
        12  + 64 =
             76

b) x³ - x² - 2 x   -> para x = -2
 (-2)³ - (-2)² - 2 .(-2) =
 - 8   -   4    + 4 =
            - 8

c) 5 x   -> para x = -3
      5 . (-3) =
        - 15

d)  1, 5 x² + x - 3,2  -> para x = 2
      1,5 . 2² + 2 - 3,2 =
       1,5 . 4 + 2 - 3,2 =
           6 + 2 - 3,2 =
               8 - 3,2 =
                4,8
Bom, se for isso mesmo que entendi, espero ter ajudado.  \pi ;)
1 4 1